Manajemen Koleksi Buku Perpustakaan dalam Mendorong Minat Baca di SMAN 1 Langkaplancar - Cici Rasmanah; Irwan Nurjamiludin; Irpan Ilmi (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
The school year is an important period in student growth and development. At this age, it is the right time to instill good habits in students. If instilled from an early age, these good habits will stick with students until adulthood. Small habits such as reading can be started early. At SMAN 1 Langkaplancar a reading corner has been provided for students' reading activities in class, but the existence of a student reading corner in this class has not been fully optimized by students. This research method uses qualitative research with a case study approach which aims to examine the condition of objects naturally. Data collection techniques in the data collection procedures in this research are participant observation, in-depth interviews and document collection. Data collection techniques in this research use observation and interview techniques on research objects, research by means of observation and interviews respectively using research instruments. One of the supports needed to foster students' interest in reading at school is the role of the teacher. Teachers need to motivate students to love books from the start. The advantages of a school library include being a source of teaching and learning activities, namely helping educational and teaching programs in accordance with the objectives contained in the curriculum, helping students to expand their knowledge, developing an interest and reading culture that leads to independent learning habits.